Electrocoagulation of quinone pigments - Chairungsi N. (2014)
Some representative quinones, viz. one naphthoquinone (plumbagin) and five anthraquinones (alizarin, purpurin, chrysazin, emodin, and anthrarufin), were subjected to electrocoagulation. It was found that the rate and extent of coagulation of these compounds appears to correlate with the number and relative position of their phenolic substituent groups, and that all of the coagulated quinones could be recovered. Attempts were then made to electrochemically isolate three quinones, namely plumbagin, morindone and erythrolaccin, from natural sources. © 2006 by MDPI.